(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
For effective teaching-learning process in any institution of learning, suitable conditions of both teaching materials and environmental condition are of paramount importance. Environmental condition plays a vital role, positively or otherwise, in effective teaching-learning process. This study surveyed phanerophytes on federal college of education (Technical), Gombe campus. Four sites were selected using deliberate sampling technique namely, Administrative block, Students’ hostels, Classes area and Staff quarters. Results obtained identified 14 different species of phanerophytes belonging to 11 families with the highest record of species diversity at Staff quarters. Higher values of relative density, basal area, relative dominance and importance value indices were recorded on Azadirachta indica and Parkia biglobosa. Importance value indices suggested Azadirachta-Parkia type of vegetation complex on the college campus. Introduction of exotic species in afforestation program was recommended for FCET, Gombe so as to increase the vegetation cover of the college campus among other recommendations.